2015
DOI: 10.2176/nmc.oa.2015-0126
|View full text |Cite
|
Sign up to set email alerts
|

Choroid Plexus Tumors: Experience of 10 Cases with Special References to Adult Cases

Abstract: Choroid plexus tumors (CPTs) are rare intraventricular neoplasms accounting for about 0.3–0.6% of all intracranial tumors. This retrospective study on CPTs presents clinico-pathological features and management strategies based on a 20-year single-institutional experience. This series included 10 consecutive patients with pathologically proven CPTs; 5 choroid plexus papillomas (CPPs), 3 atypical CPPs (ACPPs), and 2 choroid plexus carcinomas (CPCs). Their clinical, radiological, and histopathological features as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Eight of the studies included pediatric patients, 13–15 , 27 , 29 , 30 , 33 , 36 and only 2 studies totally consisted of the adult patient population. 28 , 32 Also, 4 studies had a mixed pediatric and adult population 26 , 31 , 34 , 35 with only one of them providing individual patient data for separate data extraction for the pediatric and adult populations 31 ( Table 1 ). To prevent readers from getting confused by these heterogeneous types of studies with different included populations, we developed a strategy to demonstrate the results of these populations separately within tables.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight of the studies included pediatric patients, 13–15 , 27 , 29 , 30 , 33 , 36 and only 2 studies totally consisted of the adult patient population. 28 , 32 Also, 4 studies had a mixed pediatric and adult population 26 , 31 , 34 , 35 with only one of them providing individual patient data for separate data extraction for the pediatric and adult populations 31 ( Table 1 ). To prevent readers from getting confused by these heterogeneous types of studies with different included populations, we developed a strategy to demonstrate the results of these populations separately within tables.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 14 included studies, the overall chemotherapy regimen or radiotherapy protocol had been indicated in only 4 studies. 15 , 29 , 31 , 34 Even in these 4 studies, the significant details of the adjuvant treatment protocol were missing. The most used chemotherapeutic agents were Etoposide, Vincristine, Cisplatine, Cyclophosphamide, or Ifosfomide but other agents such as Carboplatine or Thalidomide were also mentioned.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For lateral and 3rd ventricle CPCs, the median age of presentation is 1.5 years, and supratentorial CPCs are extremely rare in adults. In fact, we could only retrieve 4 cases from the literature [891011], which are summarized in Table 1. The second case presented here was diagnosed at age 49, and the location of the tumor was more consistent with ‘extraventricular’ than lateral ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…In children, they frequently arise from the lateral ventricles and the fourth ventricle in adults. Rarely, they occur in the cerebellopontine angle (CPA), suprasellar region, or even in the sacral canal [3]. To the author's knowledge, we present the first adult case of CPC presenting in the CPA.…”
Section: Introductionmentioning
confidence: 96%